2022
DOI: 10.1097/md.0000000000028393
|View full text |Cite
|
Sign up to set email alerts
|

The analysis of root canal curvature and direction of maxillary lateral incisors by using cone-beam computed tomography

Abstract: The aim of this study was to investigate root canal curvature and direction of maxillary lateral incisors in Shandong, China. Cone beam computed tomography (CBCT) images of 176 maxillary lateral incisors of 88 patients were collected in Shandong Province, China. Software included with CBCT was used to measure the angle of root canal curvature of maxillary lateral incisors on the maximum bending plane. In addition, the direction of each root canal was recorded. The data were statistically analyzed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…Curvature rates of the first molar did not differ significantly from the second molar which is consistent with results found by Levenets et al 39 in the Krasnoyarsk population. No differences were observed in the variance of the mean angle of root canal curvature between the left and right sides (p > .05) which is consistent with Wang et al 9 and Tzeng et al who asserted symmetry in bilateral maxillary molars. 40 In summary, root canal curvature in maxillary posterior teeth varies in the Egyptian population, hence raising treatment difficulty.…”
Section: Asdj Ain Shams Dental Journalsupporting
confidence: 89%
See 1 more Smart Citation
“…Curvature rates of the first molar did not differ significantly from the second molar which is consistent with results found by Levenets et al 39 in the Krasnoyarsk population. No differences were observed in the variance of the mean angle of root canal curvature between the left and right sides (p > .05) which is consistent with Wang et al 9 and Tzeng et al who asserted symmetry in bilateral maxillary molars. 40 In summary, root canal curvature in maxillary posterior teeth varies in the Egyptian population, hence raising treatment difficulty.…”
Section: Asdj Ain Shams Dental Journalsupporting
confidence: 89%
“…8 Earlier studies applied different approaches to determine root canal curvature involving periapical radiography, transparent tooth techniques, and microcomputed tomography. 9 In 2008, Estrela et al 10 suggested the utilization of cone beam computed tomography (CBCT) for finding anatomical and pathological changes, as opposed to periapical radiography, which fails to show curvatures in a three-dimensional direction.…”
Section: Introductionmentioning
confidence: 99%